Spatial variation in physical and chemical parameters and benthic macro-invertebrate fauna of River Ogunpa, Ibadan (2005)
A fluviatile ecosystem, River Ogunpa, was studied between the months of May and July 2000, to assess spatial variations in physical and chemical parameters and benthic macro-invertebrate faunal composition. Water and qualitative benthic samples were collected four times from five stations located along the river for laboratory analysis. High mean value of biochemical oxygen demand (BOD) of 20.15 ± 4.18 mgO2/l, chemical oxygen demand (COD) of 121.95 ± 19.04 mg02/l ammonia of 1.53 ± 0.44mg/l, total suspended solids (TSS) of 152.2+12.85mg/l, lead of 0.126 ± 0.06mg/l, copper of 0.3+0.07mg/l and zinc of 0.49 ± 0.07mg/l were recorded. Analysis of variance (ANOVA) showed significant differences (P<0.05) in mean values of pH, dissolved oxygen (DO), COD, turbidity, iron and copper from the five stations. Six benthic macroinvertebrate fauna; Melanoides tuberculata, Physa waterloti, Bulinus globosus, Tubifex spp; Chironomus spp and Brachydeutera spp. were recorded. The result showed that the river is under pollutional stress from oxygen demanding organic wastes. Heavy metals analyzed show that lead, copper and zinc levels may be increasing to dangerous levels in the river. Spatial variations along the river showed some stations to be more polluted than others. All the benthic macro-invertebrate fauna recorded were pollution tolerant species.